Effect of Prostaglandins F2 on the Evaluation of Vaginal Epithelial Cells of Iraqi Ewes during Puerperium - Zaid, Nazih Wayes (The Iraqi Journal of Veterinary Medicine, 2006)
This study was carried on 24 adult multipara Iraqi ewes in experimentalfarm related to College of Veterinary Medicine, University of Baghdad during2005. This study revealed the effect of prostaglandin F2 during puerperiumperiod through the evaluation of vaginal epithelial cells by using vaginal smearmethods. Intramuscular injection of 1 ml prostaglandin F2 (Iliren®) (tiaprosttrometamol=0.196mg) was done in the 4th days after parturition to 12 ewes. Thevaginal smears were taken in the 4th, 16th and 28th days. Histologicalexamination revealed that the intermediate epithelial cells were a predominant.Keratinized cells were takes place in all epithelial cells. Vacuolations werepresent in the cytoplasm of epithelial cells, meanwhile presence of WBCs in the16th and 28th days were obvious. This indicates the benefit usage ofprostaglandin F2 during puerperium period to accelerate ovarian rebound